(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Background: Postoperative Cognitive Dysfunction (POCD) is a significant and common complication following surgical procedures, particularly in the elderly population. It is characterized by a decline in cognitive domains such as memory, attention, and executive function, persisting for weeks or months after surgery. The role of anaesthesia in the pathogenesis of POCD remains a subject of intense research and debate, involving a complex interplay of pharmacological, inflammatory, and patient-specific factors. Objectives: This paper aims to comprehensively review the current evidence regarding the impact of different aesthetic techniques and agents on the incidence and severity of POCD in elderly patients. We will explore proposed mechanisms, risk factors, and potential preventive strategies. Methods: A narrative review of the literature was conducted using databases such as PubMed, Scopus, and Cochrane Library, focusing on clinical trials, meta-analyses, and review articles published between 2000 and 2023. Results: Evidence suggests that no single anaesthetic agent is definitively superior in preventing POCD. However, anaesthetic management strategies appear to be influential. Key factors include the depth of anaesthesia, the use of multimodal analgesia to minimize opioid consumption, and the potential neuroprotective benefits of regional anaesthesia techniques. The pathophysiology is multifactorial, with neuroinflammation, neuronal apoptosis, and disruption of neurotransmitter systems (particularly cholinergic) playing central roles. Patient-related factors, such as pre-existing cognitive impairment, advanced age, and comorbidities, are the strongest predictors of POCD. Conclusions: Anaesthesia contributes to POCD through direct and indirect mechanisms. A tailored, geriatric-focused anaesthetic plan that emphasizes hemodynamic stability, minimal sedative exposure, and aggressive management of perioperative inflammation may help mitigate the risk of POCD in vulnerable elderly patients. Future research should focus on biomarkers for early detection and novel neuroprotective adjuvant therapies.